EFFECT OF THE AIR FLOW RATE OF BLOWER ON THE PERFORMANCE OF SOLAR STILL - El, Emin; Argunhan, Zeki; Cakmak, Gulsah; Yucel, Halit Lutfu; Yildiz, Cengiz (Turkish Soc Thermal Sciences Technology, 2015)
Solar distillation is one of the important methods for water purification. This paper examines the performance of solar distillation system at different air flow rate. To increase the performance of distiller, artificial wind was created by fan and suitable wind speed was investigated to increase the amount of water distilled. The experiments were carried out in Elazig climate conditions. In order to examine the effect of the wind speed on solar distillation system, two stills were manufactured with the size of 1000x1000 mm. One of them was the conventional still which was used as a reference. The other still was used to investigate experimentally the effect of the wind speed. Graphs were drawn for time-dependent changes in the amount of water distilled. It was found that that the productivity of the fan-still distiller was 14.7 % greater than that of a conventional still.
Keywords: solar still; distillation; blower